Searching for New Model of Digital Informatics for Human-Computer Interaction: Testing the Institution-Based Technology Acceptance Model (ITAM) - Kang, Youngcheoul; Choi, Nakbum; Kim, Seoyong (International journal of environmental research and public health, 2021)
The fourth industrial revolution has produced new information technology (IT) that is widely used in the healthcare industry. Although the nature of the institution affects IT adoption, the Technology Acceptance Model (TAM), a dominant theory, has dismissed its role and influence. Our research investigates how institutions influence the adoption of new IT by using the Institution-based Technology Acceptance Model (ITAM). We conducted an empirical test by using survey data collected from 300 employees in the public sector. Structural equation modeling was applied to test the proposed hypotheses. The results showed the total effect of institutions on the intention to use new IT is positive and significant. Second, IT adoption is not only affected by external institutions but also by type of institution; the external institution takes a greater role in inducing perceived usefulness, perceived ease of use, and intention to use than does the internal. Third, perceived ease of use and perceived usefulness play mediating roles between institution and IT adoption. Fourth, an alternative expanded model to which more individual and organizational factors were added confirmed the results of the base model. We concluded that institutions have a strong impact on the level of intention for IT use through perceived ease of use and perceived usefulness.
Keywords: Attitude to Computers; Computers; Humans; Informatics; Intention; Technology; digital informatics; human–computer interaction; institution; institutionalism; new information technology; Technology Acceptance Model (TAM)